Variación del ciclo Biológico en la producción Masal de Coleomegilla maculata por el efecto de tres Dietas, en Laboratorio. - Silva Calongos, Llanet (2006)
The present work of investigation was carried out in the laboratory of Upbringíng of Useful insects of the National University of San Martin, located in the district of Morales, to an attitude of 390 m.s.n.m. The objectives were to evaluate the variation of the biological cycle of Coleomegílla maculata for effect of three diets and to evaluate sorne reproductive characteristics. This work began in the month of March of 2005 and it culminated at the end of August of the same year. The statistical design was of BCR, with three treatment and five repetitions, with daily evaluations, The cycle of life of Coleomeg111a maculata was of 10,81 days for larva, 3,67 days for pustule and 140,4 days for mate adult and 93,87 for female adult to a temperature average of 26,06 and a relative humidity of 78,35%. The posture capacity is expressed in the biggest number of eggs by posture and not in more number of postures, that expressed bigger number of eggs for female. Being observed that the treatment two T2 with more number of postures (25,8 eggs) she obtained less eggs for female, in front of the treatment two with 23 postures she obtained 552 eggs for female. The diets that obtaíned better results for the raising of maculata Coleomegilla are with eggs of Sitotroga carealella and pulgones of Fñjol (Aphis gossypi).